OPTIMIZATION OF Talinum paniculatum Gaertn. ROOT INDUCTION AND THE EFFECT OF PHOSPHATE CONCENTRATIONS AND AMMONIUM:NITRATE RATIO ON BIOMASS OF ADVENTITIOUS ROOTS IN IN VITRO CULTURE - Manuhara, Yosephine Sri Wulan; Palupi Dasawulan Lestari; Syifa Fajrisani; Putri Gehasti; Sugiharto (BIOTROPIA, 2023)
Java ginseng (Talinum paniculatum Gaertn.) is a medicinal plant, the roots of which are commonly used in traditional medicine. In its natural habitat, the roots grow very slowly, requiring two to three years to produce 100 g of roots per plant. Plant tissue culture could therefore provide an alternative means of accelerating root growth. This research aimed to optimize root induction and determine the effect of phosphate (KH2PO4) concentration and the ratio between ammonium and nitrate (ammonium:nitrate) on the biomass of Java ginseng adventitious roots in in vitro culture. Stem and leaf were used as explants and various combinations and concentrations of IBA and BAP, kinetin, and TDZ were used as growth regulators. Leaf explants were grown in Murashige and Skoog (MS) media supplemented with IBA 2 mg/L and various concentrations of phosphate (170; 212.5; 255; 297.5; 340; 382.5; 425; 467.5; 510 mg/L) and various ammonium:nitrate ratios (21:19 mM as the control, 0:30 mM, 10:20 mM, 15:15 mM, 20:10 mM, 30:0 mM). Cultures were maintained for 6 weeks. The observed parameters were fresh weight, dry weight, the duration of root formation, and the number and length of adventitious roots. The data were analyzed using Analysis of Variance. The results showed that the concentration of phosphate and the ammonium:nitrate ratio significantly influenced the amount, length, fresh weight, and dry weight of Java ginseng adventitious root. The highest fresh weight (37.47 mg) and dry weight (5.53 mg) were achieved in the treatment of double phosphate concentration (KH2PO4 340 mg/L), while an ammonium:nitrate ratio of 10:20 mM was the optimum treatment to produce the highest biomass (fresh weight 73.6 mg and dry weight 8.2 mg).